Climate Change as Modifier of Landslide Susceptibility: Case Study in Davao Oriental, Philippines - Beroya-Eitner, Mary Antonette A (Archīum Ateneo, 2023)
Rainfall-induced landslides are widely occurring phenomena that cause billions of US dollars annually in damage, and thousands of deaths globally. The Philippines, due to its climate, geographic location and topography, is among those countries most prone to the hazard. The strong climatic warming trend over the past decades has affected the rainfall pattern in the country, thus affecting the landslide distribution as well. This study aims to determine how the rainfall in our study area, Davao Oriental, is expected to change in the future in response to climate warming and how such a change may affect the landslide susceptibility pattern in the province. Results show that contrary to the general perception of increased landslide susceptibility due to a warming climate, a decreased susceptibility is anticipated in the study area. Despite this decrease, however, there remains high to very high landslide hazard for the northern part of the province well into the future, and risk reduction work is still needed in this area. Moreover, while the projected decrease in rainfall and landslide susceptibility is a positive sign concerning landslide hazard management, such a drying trend may spawn other hazards, including drought and water shortage, underscoring the need for a multi-hazard assessment that takes into account the complex interrelationships between different hazards. We deem the results of the study to be very important for better prioritization and more efficient allocation of resources for disaster risk management and reduction. The methodology developed for this study can be applied to other parts of the Philippines, and other regions as well.